Analysis of Public Policy and Enforcement of Domestic and Foreign Arbitral Awards in India - Dubey, Yash (Christ University Law Journal, 2018)
The Public Policy doctrine is an unruly horse in India, when it comes to the enforcement of domestic and foreign awards. The main objective behind choosing this topic was to shed light on how public policy has been used by the losing party, in delaying the enforcement of arbitral award, which hampers the whole objective of arbitration. Though one may argue that the 2015 Amendment Act has settled all the controversies regarding public policy and enforcement of arbitral award, the author is of the opinion that there are still some areas that are left unexplored by the Arbitration Amendment Act. The paper primarily focuses on the changing trend of public policy with respect to arbitration in India. In addition, the author has compared the doctrine of public policy in India with that of countries such as France, Russia, United Kingdom and U.SA. The most important contribution of this research paper is that it analyses the validity of patent illegality in domestic arbitration.